Disability and loneliness in nine countries of the former Soviet Union. Issue 4 (October 2021) - Stickley, Andrew; Kondo, Naoki; Richardson, Erica; Leinsalu, Mall; Waldman, Kyle; Oh, Hans; Inoue, Yosuke; Shakespeare, Tom; McKee, Martin
Abstract: Background: People with disabilities (PWD) often face structural and other barriers to community involvement and may therefore be at risk of loneliness. Yet, so far, this issue has received little attention. Objective: This cross-sectional study aimed to examine the association between disability and loneliness in nine countries of the former Soviet Union (FSU). Methods: Data were analyzed from 18000 respondents aged ≥18 that came from the Health in Times of Transition (HITT) survey that was undertaken in Armenia, Azerbaijan, Belarus, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Russia and Ukraine in 2010/11. Respondents reported on whether they had a disability (no/yes) and its severity. A single-item question was used to assess loneliness. Logistic regression analysis was used to examine the associations. Results: Across the countries, 6.8% of respondents reported being disabled. In a fully adjusted combined country analysis, disability was associated with higher odds for loneliness (odds ratio: 1.30, 95% confidence interval: 1.06–1.60). In an analysis restricted to PWD, individuals in the most severe disability category (Group 1) had over two times higher odds for loneliness when compared to those in the least severe disability category (Group 3). Conclusions: Disability is associated with higher odds for reporting loneliness in the FSU countries and this association is especially strong among those who are more severely disabled. An increased focus on the relationship between disability and loneliness is now warranted given the increasing recognition of loneliness as a serious public health problem that is associated with a number of detrimental outcomes.